Perbandingan Kejadian Infeksi Saluran Kemih setelah Pemasangan Kateter antara 24-36 Jam dan 36-48 Jam pada Pasien Pascaoperasi Ginekologi - Windy Puspa Kusumah; Benny Hasan Purwara; Eppy Darmadi Achmad (Indonesian Journal of Obstetrics & Gynecology Science, 2018)
AbstrakTujuan: Penggunaan kateter pada saat dilakukan operasi merupakan prosedur rutin termasuk  operasi ginekologi sehingga kandung kemih tetap kosong pada saat operasi serta mencegah jejas. Metode: Penelitian analitik komparatif dibagi menjadi 2 kelompok, pelepasan  24-36 jam dan  36-48 jam. Hasil dipstik leukosit diambil pre-operasi dan 24-36 jam dan 36-48 jam pasca-operasi. Hasil: Total terdapat 48 pasien dengan umur  antara 31-40 tahun  29.2% serta  umur 41-50 tahun 29.2%. Lama operasi  antara 1 sampai 2 jam sebanyak 54.2%. Kelompok 36-48 jam, hasil leukosit urine terbanyak (+) ada 62.5%. Pemasangan Kateter 24-36 jam yang awalnya (-) kelompok 36-48 jam menjadi (+) sebanyak 60.0%. Diskusi:Penelitian ini mengikutsertakan 63 subjek yang memenuhi kriteria inklusi sebanyak 48 orang yang dibagi menjadi dua kelompok. Pasien pascaoperasi dengan peningkatan leukosit urine ditemukan pada 57% subjek di kelompok pelepasan kateter 36-48 jam pasca operasi, sedangkan hanya 15% pada kelompok pelepasan kateter 24-36 jam pasca operasi. Kesimpulan: Pelepasan kateter pascaoperasi 36-48 jam, lebih banyak terjadi insidensi peningkatan leukosit urine dibandingkan kelompok 24-36 jam.Comparison of Urinary Tract Infections after the Insertion of Catheter between 24–36 Hours and 36–48 Hours on Post Gynecologic Surgery PatientsAbstractObjective: Use of catheter during surgery is a routine procedure in every surgery, also gynecological surgery so the bladder remains empty during surgery. Catheter may prevent iatrogenic injury of the bladder caused by over-distention and atony due to anesthesia. Method: Unpaired categorical comparative analytic study with subjects were categorized into 2 groups, groups of patients in 24-36 hours catheters and patients in 36-48 hours post-surgery catheters. Urine leukocyte dipstick taken pre-surgery, 24-36 hours and 36-48 hours post-surgery. Result: A total of 48 patients were selected for data use for this study. For the longest operation time between 1 to 2 hours as much as 54.2%. For 24-36 hours urine leukocyte with negative results as much as 75%. While in the 36-48 hours catheter insertion there were 62.5%. Increasing of urine leukocyte result at 24-36 hours catheter insertion in 36-48 hours catheter insertion group. Discussion: The study included 63 subjects divided into two groups. Post-surgery patients with elevated urinary leukocytes were found in 57% of subjects in the 36-48 hours post-surgery catheter release group, while only 15% in the 24-36 hours catheter release group.Conclusion: Post-surgery catheters 36-48 hours, there was a greater incidence of urinary leukocyte increment than the group of patients with 24-36 hours post-surgery catheters.Key words: Urinary tract infection, pre-surgery catheter, post-surgery catheter.